The Alaska-Siberia connection : the World War II air route - Hays, Otis, 1915- (Texas A & M University military history series, 1996)
American Lend-Lease generosity helped to join Russia and America in a wartime alliance against Germany. However, Russia, suspicious of American sincerity, delayed the establishment of an Alaska-Siberia delivery route (known throughout the war as ALSIB) to the German war front. Instead, other routes via the North Atlantic and the Persian Gulf were employed for the delivery of urgently needed aircraft in 1941-42. Eventually, recognizing that an ALSIB route would allow the.